Main Parameters On The Performance Of A Desulfurization Of Ferro-Nickel By Slag Reaction - M. Hochenhofer (The Minerals, Metals and Materials Society, 2005)
Keywords: desulfurization, mathematical model, slag reaction To produce ferroalloys like ferro-nickel for alloying purposes in a quality that meets the requirements of today?s steel industry, refining processes like desulfurization and dephosphorization are indispensable. The performance of desulfurization-treatment by slag reaction depends on various parameters, such as: sulfide capacity and viscosity of the slag, sulfur distribution between metal and slag, activity of sulfur in melt and movement of melt. Within this work, the combined influences of these parameters on the desulfurization of a ferro-nickel alloy were examined. As a basis for this examination, a mathematical model, based on data from plant trials, was created. This model demonstrates the relationship between desulfurization rate and initial values of the above mentioned parameters. With this model the relevant parameters were evaluated and assessed concerning their influence on desulfurization.